DNMT1 and Sp1 competitively regulate the expression of BACE1 in A2E-mediated photo-oxidative damage in RPE cells. (December 2018) - Huang, Peirong; Sun, Junran; Wang, Fenghua; Luo, Xueting; Zhu, Hong; Gu, Qing; Sun, Xiangjun; Liu, Te; Sun, Xiaodong
Abstract: Numerous studies have focused on the deteriorate role of amyloid-β (Aβ) on retina, implying the potential pathogenic mechanism underlying age-related macular degeneration (AMD). However, the mechanism underlying the Aβ deposition in AMD patients remains unknown. Beta-site amyloid precursor protein-cleaving enzyme 1 (BACE1), rate-limiting enzyme for Aβ production, plays an important role in Aβ deposition in the brain. In the current study, we aimed to clarify the regulation mechanism of BACE1 and explore potential drug targets using a lipofuscinfluorophore A2E-mediated photo-oxidation model. In this model, Aβ1-40 and Aβ1-42 levels increased simultaneously with the enhanced BACE1 expression. These changes were associated with the hypomethylation of specific loci within the BACE1 gene promoter and the decreased levels of DNA methyltransferase 1 (DNMT1). Furthermore, we noticed overlapping regions of differentially methylated CpG islands and specificity protein (Sp1) binding sites within the BACE1 promoter. We employed chromatin immunoprecipitation (ChIP) assay to verify that the decreased BACE1 promoter methylation by DNMT1 enabled increased binding between Sp1 and the BACE1 promoter, which further enhanced BACE1 transcription. The inhibition of Sp1 with mithramycin A (MTM) could down-regulate the expression of BACE1 as well as alleviate the RPE barrier morphology and function impairment. Our results for the first time show the competitive regulation of BACE1 by transcription factor Sp1 and DNMT1 after photo-oxidation and confirm the potential novel protective role of MTM on RPE cells. Highlights: Our study provided novel insight into the mechanism of Aβ accumulation in the retina after A2E-mediated photo-oxidation. In this model, the transcription of BACE1 was competitively regulated by transcription factor Sp1 and DNMT1. We firstly found the potential protective effect of Sp1 inhibitor MTM on RPE cells.